Resilience as a Moderator of Perceived Stress and Coping Strategies in Sophomore College Students Post-COVID-19 Pandemic - Petrick Pratama; Marselius Sampe Tondok (Kuras Institute, 2023)
The post-COVID-19 pandemic has had various impacts on human life, including on educational institutions and sophomore students. One of the negative consequences has been an increase in perceived stress, which has necessitated the development of coping strategies. Resilience is believed to play a significant role in influencing the quality of these coping strategies. This research aims to examine the moderating influence of resilience on coping strategies for perceived stress among sophomore students in the post-COVID-19 pandemic era. Participants included students in their third to sixth semesters, selected through snowball sampling. Data were collected via an online questionnaire encompassing three scales: Brief COPE, Perceived Stress Scale (PSS), and Brief Resilient Coping Scale (BRCS). Data analysis involved descriptive analysis and moderated regression analysis. The study concludes that resilience significantly moderates the relationship between coping strategies and perceived stress (t = -10.722, p < 0.05). The theoretical and practical implications of these findings are further discussed.